1995
DOI: 10.1016/0092-8674(95)90531-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor NF-E2 is required for platelet formation independent of the actions of thrombopoeitin/MGDF in megakaryocyte development

Abstract: Despite the importance of blood platelets in health and disease, the mechanisms regulating their formation within megakaryocytes are unknown. We generated mice lacking the hematopoietic subunit (p45) of the heterodimeric erythroid transcription factor NF-E2. Unexpectedly, NF-E2-/- mice lack circulating platelets and die of hemorrhage; their megakaryocytes show no cytoplasmic platelet formation. Though platelets are absent, serum levels of the growth factor thrombopoietin/MGDF are not elevated above controls. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
538
1
8

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 693 publications
(569 citation statements)
references
References 53 publications
22
538
1
8
Order By: Relevance
“…Each heterodimer binding appeared as a doublet (Fig. 5C, lanes 3, 8, and 13), probably due to the presence of two isoforms of p45 (31), which is consistent with our previous result showing a doublet MAREbinding activity composed of p45 and small Maf in megakaryocytes (20).…”
Section: Smallsupporting
confidence: 81%
See 1 more Smart Citation
“…Each heterodimer binding appeared as a doublet (Fig. 5C, lanes 3, 8, and 13), probably due to the presence of two isoforms of p45 (31), which is consistent with our previous result showing a doublet MAREbinding activity composed of p45 and small Maf in megakaryocytes (20).…”
Section: Smallsupporting
confidence: 81%
“…Genetic and biochemical studies have revealed that the small Maf-p45 heterodimer, which is also known as NF-E2, serves as an indispensable transcriptional activator for terminal megakaryocyte differentiation (17,24,29,31). The megakaryocytes of p45-null mutant mice proliferate and differentiate in response to thrombopoietin, without practically any proplatelet generation.…”
mentioning
confidence: 99%
“…The results of a gene knockout experiment recently indicated that p45 is essential for platelet formation (Shivdasani et al, 1995), whereas MafK (the p18 subunit) appears to be dispensable for normal hematopoiesis as well as other developmental programs (Kotkow and Orkin, 1996). Considering the present results, not only MafK but also other small Maf proteins may contribute to the small p18 subunit of NF-E2.…”
Section: Discussionmentioning
confidence: 99%
“…Gene targeting has revealed distinct roles for several CNC family members in mammalian gene regulation. Homozygous disruption of p45 NF-E2 gene in mouse results in defective megakaryopoiesis and profound thrombocytopenia, leading to postnatal death (Shivdasani et al, 1995). Nrf-1-null mutant mice are anemic due to a noncell autonomous defect in de®nitive erythropoiesis and die in utero (Chan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%